ANALISIS IMPLEMENTASI KECAKAPAN ABAD 21 PADA MATA PELAJARAN ILMU PENDIDIKAN ALAM (IPA) DI SMP - Vitrani, Vitrani; Rahim, Hj. Sahriah; Nasir, Muhammad (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Education today is more directed at mastering 21st century skills, namely learning and innovation skills. This research uses a qualitative approach with descriptive analytics. Qualitative research is a research procedure that produces data in the form of speech, and behavior that can be observed or written. This research aims to describe the implementation of 21st-century skills in preparing lesson plans, implementing learning, and describing the implementation of 21st-century skills in evaluating science learning at State Middle Schools in Tempe sub-district. Based on the results of reviewing the RPP documents at Tempe District Public Middle School and the results of interviews conducted by researchers, it can be concluded that the implementation of 21st-century skills has been implemented at Sengkang 1 Public Middle School and Sengkang 3 Public Middle School, especially in science subjects. 21st-century skills have been outlined in every aspect of the RPP, implementation of learning, and assessment of learning outcomes. This implementation has a positive impact on teachers and students involved in implementing 21st-century skills.